2020
DOI: 10.3390/resources9120148
|View full text |Cite
|
Sign up to set email alerts
|

Producing Omega-3 Polyunsaturated Fatty Acids: A Review of Sustainable Sources and Future Trends for the EPA and DHA Market

Abstract: Omega-3 polyunsaturated fatty acids (Omega-3 PUFA) are recognized as being essential compounds for human nutrition and health. The human body generates only low levels of Omega-3 PUFA. Conventional sources of Omega-3 PUFA are from marine origin. However, the global growth of population combined with a better consumer understanding about healthy nutrition leads to the fact that traditional sources are exhausted and therefore not enough to satisfy the demand of Omega-3 PUFA for human diet as well as aquaculture.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
87
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(91 citation statements)
references
References 92 publications
0
87
0
4
Order By: Relevance
“…A total annual worldwide demand of PUFA was calculated at over 1.27 million tonnes [ 7 ]. In 2019, the global ω-3 market size was evaluated at USD 2.49 billion and a 7% increase is expected over the period 2020–2027 [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A total annual worldwide demand of PUFA was calculated at over 1.27 million tonnes [ 7 ]. In 2019, the global ω-3 market size was evaluated at USD 2.49 billion and a 7% increase is expected over the period 2020–2027 [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Highly unsaturated fatty acids (HUFA) are responsible for survival, maintaining high growth and reproductive rates, as well as high food conversion rates in both marine and freshwater organisms [79]. Arachidonic acid (ARA), eicosapentaenoic acid (EPA), and docosahexaenoic acid (DHA) are examples of HUFA-derived omega-6 (n-6) and omega-3 (n-3) FA typically found in marine fish sources; they originate from the phytoplankton and seaweed that are part of their food chain [80,81]. Several studies have demonstrated that DHA, EPA, and ARA play important roles in the survival and growth of decapod larvae, where a deficit of HUFAs may result in poor growth, lower survival, and prolonged intermolt periods [82].…”
Section: Lipidsmentioning
confidence: 99%
“…There are many studies that reflect the importance of these fatty acids in health. Antiinflammatory properties; positive effects on cardiovascular and vision health, diabetes, cancer, immune system improvement, and development of the nervous system; reduced risk of Alzheimer's diseases; and better digestibility are among their recognized properties [12][13][14]. It is important to note their ability to lower plasma triacylglycerol (TAG) (Figure 1).…”
Section: Introductionmentioning
confidence: 99%